3D Heteroatom‐Doped Carbon Nanomaterials as Multifunctional Metal‐Free Catalysts for Integrated Energy Devices. Issue 13 (14th February 2019) - Paul, Rajib; Du, Feng; Dai, Liming; Ding, Yong; Wang, Zhong Lin; Wei, Fei; Roy, Ajit
Abstract: Sustainable and cost‐effective energy generation has become crucial for fulfilling present energy requirements. For this purpose, the development of cheap, scalable, efficient, and reliable catalysts is essential. Carbon‐based heteroatom‐doped, 3D, and mesoporous electrodes are very promising as catalysts for electrochemical energy conversion and storage. Various carbon allotropes doped with a variety of heteroatoms can be utilized for cost‐effective mass production of electrode materials. 3D porous carbon electrodes provide multiple advantages, such as large surface area, maximized exposure to active sites, 3D conductive pathways for efficient electron transport, and porous channels to facilitate electrolyte diffusion. However, it is challenging to synthesize and functionalize isotropic 3D carbon structures. Here, various synthesis processes of 3D porous carbon materials are summarized to understand how their physical and chemical properties together with heteroatom doping dictate the electrochemical catalytic performance. Prospects of attractive 3D carbon structural materials for energy conversion and efficient integrated energy systems are also discussed. Abstract : Carbon‐based, heteroatom‐doped, 3D, and mesoporous materials are capable of metal‐free electrocatalysis for efficient energy conversion and storage. Different allotropes of carbon doped with a variety of heteroatoms are utilized for cost‐effective 3D electrocatalyst fabrication. Templated chemical vapor deposition and 3D printing have been recently utilized for achieving suitable 3D architectures. Such hierarchical carbon architectures demonstrate multifunctional integrated energy storage applications.